PENERIMAAN FINANCIAL TECHNOLOGY BERBASIS TECHNOLOGY ACCEPTANCE MODEL (TAM) - Sutrisno Sutrisno; Diva Riza FAHLEFI; Sarbullah Sarbullah (JURNAL STIE SEMARANG, 2020)
Tecnology Acceptance Model (TAM) developed by Davis which is a successful and acceptable model in order to predict the acceptance of a new technology. In the last two years, in Indonesia there has emerged a financial technology service that was designed with the open platform principle, OVO. OVO is a service engaged in the field of financial technology, is a smart application designed to make payment services and transactions online, and has penetrated into all business expansion. The purpose of this research is to find out. the effect of perceived ease, perceived risk and attitude of use on the intention of OVO financial technology behavior in Surakarta City. The population used in this study were all users who intended to use OVO financial technology behavior in Surakarta City amounted to 140. The sample used in this study were 60 people. Data analysis methods used are descriptive statistical analysis, validity test, Classic Assumption Test, multiple regression analysis, t-test statistics and the model feasibility test and the coefficient of determination. The results of this study indicate that perceptions of ease have a positive and significant influence on the behavioral intention of OVO financial technology in the city of Surakarta with a significance of 0,000 <0.05. perceived risk has a positive and significant effect on the intention of OVO financial technology behavior in Surakarta City with a significance of 0.002 <0.05. usage attitude has a positive and significant influence on the intention of OVO financial technology behavior in Surakarta City with a significance of 0,000 <0.05. This means that all variables affect the intention of OVO financial technology behavior in Surakarta City. Seeing the results of the research conclusions, that Behavioral Intetion of the users stated that those interested in using OVO financial technology applications with the advantages offered such as free transfers